2019
DOI: 10.1242/dmm.037226
|View full text |Cite
|
Sign up to set email alerts
|

The zebrafish orthologue of the human hepatocerebral disease geneMPV17plays pleiotropic roles in mitochondria

Abstract: Mitochondrial DNA depletion syndromes (MDS) are a group of rare autosomal recessive disorders with early onset and no cure available. MDS are caused by mutations in nuclear genes involved in mitochondrial DNA (mtDNA) maintenance, and characterized by both a strong reduction in mtDNA content and severe mitochondrial defects in affected tissues. Mutations in MPV17 , a nuclear gene encoding a mitochondrial inner membrane protein, have been associated with hepatocerebral forms of MDS. The ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…The roy strain has a spontaneous mutation that leads to complete iridophore defects and a transparent trunk [5,8,9]. As both casper and roy mutants have the same phenotype of iridophore loss, they were treated as the same transparent group.…”
Section: Gwas and Transcriptome Results For Iridophore Lossmentioning
confidence: 99%
See 2 more Smart Citations
“…The roy strain has a spontaneous mutation that leads to complete iridophore defects and a transparent trunk [5,8,9]. As both casper and roy mutants have the same phenotype of iridophore loss, they were treated as the same transparent group.…”
Section: Gwas and Transcriptome Results For Iridophore Lossmentioning
confidence: 99%
“…A mpv17-knockdown zebrafish exhibited a moderate loss of iridophores along the body axis [8]. A recent study [9] further demonstrated that the mpv17 −/− zebrafish knockouts exhibited iridophore loss. It was therefore postulated that the mpv17 gene in zebrafish could play a key role in pyrimidine synthesis for iridophore development and maintenance [9].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…To search for possible modifier genes responsible of the phenotype anticipation, we first analysed two genes previously proposed to modify the severity of the clinical phenotype in some mouse models of mitochondrial dysfunction, i.e. Prkdc, encoding for the catalytic subunit of the DNA-dependent protein kinase (DNA-PK) (Papeta et al, JCI 2010), and Nnt, encoding the nicotinamide nucleotide transhydrogenase (McManus et al, 2019). However, the Prkdc mutation described in Balb/c and other inbred strains was not present in our C57Bl/6 colonies, and the Nnt mutation, present in the of pure C57Bl/6J strain, did not segregate with the disease (not shown).…”
Section: Early Onset Kidney Disease In Mpv17 -/Micementioning
confidence: 99%
“…Other data showed that reduced MPV17 expression was associated with impaired dTMP synthesis without affecting de novo or salvage synthesis of dTMP, suggesting that MPV17 may be involved in maintaining dTMP levels in mitochondria through a still uncharacterized pathway, which may be involved in transporting dTMP or one of its precursors from the cytosol to mitochondria (Alonzo et al, 2018). In zebrafish, Mpv17 has been related to pyrimidine nucleotide metabolism via impairment of dihydroorotate dehydrogenase (Martorano et al, 2019). All these observations have been reported in single publications and do need further confirmation.…”
Section: Introductionmentioning
confidence: 99%